The Effect of Binahong Leaf Gel (Anredera cordifolia) with the Addition of HPMC (Hydroxy Propyl Methyl Cellulose) on Wound Area Reduction and Angiogenesis in the Skin of Mice (Mus musculus) with Second-Degree Burns - Hartyastika, Silvi Ayuk; Holil, Kholifah (El-Hayah:Jurnal Biologi, 2023)
Second-degree burn injuries are a form of tissue damage to the skin and its structures that need to be addressed. One medicinal plant that can be used to treat burn injuries is the Binahong plant (Anredera cordifolia). Therefore, this study aims to determine the effect of Binahong leaf gel with the addition of HPMC on wound area reduction and angiogenesis. The type of research used in this study is true experimental, consisting of 5 treatments: negative control (K-, without ointment and Binahong leaf extract gel), positive control (K+, treated with bioplacenton ointment), treatment 1 (P1, treated with Binahong leaf gel with 6.7 grams extract), treatment 2 (P2, treated with Binahong leaf gel with 8 grams extract), and treatment 3 (P3, treated with Binahong leaf gel with 12 grams extract). The mice given various treatments were observed every 2 days until the 14th day to observe scab formation. Other parameters observed in this study include wound area reduction and angiogenesis after treatment. The data obtained were tested with ANOVA and followed by LSD test at α 0.05. The results showed that Binahong leaf gel (Anredera cordifolia) with the addition of HPMC affected wound area reduction and angiogenesis, with the most optimal results found in P3 (Binahong leaf gel with 12 grams extract).